Application of immune checkpoint inhibitors for resectable gastric/gastroesophageal cancer - Lin, Feizhi; Chen, Yongming; Huang, Bowen; Ruan, Shenghang; Lin, Jun; Chen, Zewei; Huang, Chunyu; Zhao, Baiwei (Frontiers in Pharmacology, 2024)
Gastric /gastroesophageal junction (G/GEJ) cancer represents a significant global health challenge. Radical surgery remains the cornerstone of treatment for resectable G/GEJ cancer. Supported by robust evidence from multiple clinical studies, therapeutic approaches, including adjuvant chemotherapy or chemoradiation, and perioperative chemotherapy, are generally recommended to reduce the risk of recurrence and enhance long-term survival outcomes post-surgery. In recent years, immune checkpoint inhibitors (ICIs) have altered the landscape of systemic treatment for advanced or metastatic G/GEJ cancer, becoming the standard first-line therapy for specific patients. Consequently, exploring the efficacy of ICIs in the adjuvant or neoadjuvant setting for resectable G/GEJ cancer is worthwhile. This review summarizes the current advances in the application of ICIs for resectable G/GEJ cancer.